DEVELOPMENT STRATEGY FOR QUALITY CHARACTER THROUGH STANDARDIZATION OF SMEs (Case Study In Culinary SMEs) - Rediawan Miharja (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
e importance of the role of SMEs in the regional, national, and global economy as well as the industrial era 4.0, which requires business actors to continue to be able to innovate, It needs encouragement from various groups, including academics, on how to make conceptualizations that can be used as material for policies or decisions for business actors or stakeholders. Along with the growing awareness of SMEs about competitiveness because they are facing the millennial era, this is an opportunity for researchers to present conceptual strategies so that they can be useful for SMEs. The problems in this study are that there is no concept that describes internal and external conditions, and the quality of SME products is inconsistent for markets that enjoy them. The purpose of this research is to build a concept of character development strategy for product quality that is always maintained so that it can become competitive in the business. The method in this study employs a qualitative approach, with tools such as Internal Factor Evaluation, External Factor Evaluation, SWOT Analysis, and problem solving using one of the standardization tools used. The results of this study show that clear work steps will make it easier for SMEs players to provide consistency in the taste that characterizes the products being marketed